Glycogen, poly(3-hydroxybutyrate) and pigment accumulation in three Synechocystis strains when exposed to a stepwise increasing salt stress - Meixner, K; Daffert, C; Dalnodar, D; Mrázová, K; Hrubanová, K; Krzyzanek, V; Nebesarova, J; Samek, O; Šedrlová, Z; Slaninova, E; Sedláček, P; Obruča, S; et al. (Journal of applied phycology, 2022)
The cyanobacterial genus Synechocystis is of particular interest to science and industry because of its efficient phototrophic metabolism, its accumulation of the polymer poly(3-hydroxybutyrate) (PHB) and its ability to withstand or adapt to adverse growing conditions. One such condition is the increased salinity that can be caused by recycled or brackish water used in cultivation. While overall reduced growth is expected in response to salt stress, other metabolic responses relevant to the efficiency of phototrophic production of biomass or PHB (or both) have been experimentally observed in three Synechocystis strains at stepwise increasing salt concentrations. In response to recent reports on metabolic strategies to increase stress tolerance of heterotrophic and phototrophic bacteria, we focused particularly on the stress-induced response of Synechocystis strains in terms of PHB, glycogen and photoactive pigment dynamics. Of the three strains studied, the strain Synechocystis cf. salina CCALA192 proved to be the most tolerant to salt stress. In addition, this strain showed the highest PHB accumulation. All the three strains accumulated more PHB with increasing salinity, to the point where their photosystems were strongly inhibited and they could no longer produce enough energy to synthesize more PHB.